Ethical fashion: An investigation into the role of ethical brands within the South African fashion retail industry. - Mkhize, Senamile (The IIE, 2020)
This research report explores the role ethical brands play within the South African fashion retail industry. The aim was to analyse consumers’ buying behaviour particularly of millennials and the factors that influence consumers’ to shopping ethically. Data for this research was collected using a qualitative research approach, with email interviews and an online survey. Secondary research was also utilised to help gain more understanding of a meaningful and strong brand and international ethical fashion brands. The findings were then sort into themes that provided insight on consumers and their attitude towards fashion brands. The central purpose for conducting this research was to gauge how perceptive South Africans’ are about ethical fashion and fast fashion. To educate them on the significance of ethical fashion. To determine an estimate of how many actually practice ethical shopping. And to identify if any of the South African fashion brands communicate with their consumers regarding where their clothes are made, who made them or even where they were sourced. The outcome from the primary research demonstrates that a large number of South Africans are not aware of what ethical fashion is. And those who are aware, are hindered by many my different factors that sometimes prevents them from practice shopping ethical.
Keywords: Fashion brands; Retail industry; Consumer purchase behaviour; Millennials; Generation Z